Identification of resistant microorganisms and microbial activity in contaminated soils under three bioremediation approaches - Salinas, A. (2024)
The success of a bioremediation process primarily depends on the intrinsic ability of the system to create and maintain conditions to promote the biodegradation of contaminants at a sufficiently high rate. Strategies to accelerate the biodegradation of hydrocarbons and other compounds in the soil include stimulating indigenous microorganisms (bio-stimulation) by optimizing factors such as the inoculation of a mixed microbial culture in the soil (bio-augmentation). The aim of this work was to identify effluent-resistant strains isolated from a landfarming and to evaluate three bioremediation approaches for a soil contaminated with glycols. For this, a series of laboratory-scale experiments were carried out with different experimental conditions: natural attenuation, biostimulation and bioaugmentation with previously selected native strains. The strains selected in previous studies were cultivated into LB-glucose (g L-1): NaCl 5.0; yeast extract 5.0; peptone 10.0; Glucose 10.0. The identification was realized by molecular techniques: DNA was obtained using a biology kit; PCR amplification with universal primers the DNA concentration in the PCR products was determined using Epoch (Biotek) and the integrity of the samples was evaluated through 1% Agarose gel electrophoresis. The PCR products were sent to CERELA (Tucuman-Argentina) for their purification and sequencing. The sequences were edited with Molecular Evolutionary Genetics Analysis (MEGA v7.0) and were analyzed with BLASTn using NCBI databases (www.ncbi.nlm.nih.gov). For the microbial activity test, 70 grams of soil were weighed in glass jars. Then, 4 ml of distilled water and 3 drops of Bromothymol Blue1 indicator were placed in the test tubes. The assembly of the devices was completed and then a “control” jar was made without the soil, to ensure that the change produced in the indicator was due to microbial respiration. The selected microorganisms were identified as coming: Penicillium, Bacillus and Acinetobacter. In the microbial activity test, different shades from yellow to green pH (6.7/7.4) could be seen: the one that received the mixed crop sowing presented lower pH values, indicating higher concentrations of CO2 coming from microbial respiration, followed by the biostimulation process and finally the natural attenuation process. Therefore, bioaugmentation and biostimulation increased microbial activity, indicating improved landfarming performance.